2014
DOI: 10.4103/2153-3539.126153
|View full text |Cite
|
Sign up to set email alerts
|

Color standardization in whole slide imaging using a color calibration slide

Abstract: Background:Color consistency in histology images is still an issue in digital pathology. Different imaging systems reproduced the colors of a histological slide differently.Materials and Methods:Color correction was implemented using the color information of the nine color patches of a color calibration slide. The inherent spectral colors of these patches along with their scanned colors were used to derive a color correction matrix whose coefficients were used to convert the pixels’ colors to their target colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
82
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(82 citation statements)
references
References 35 publications
0
82
0
Order By: Relevance
“…The staining correction we presented in this paper can be used in conjunction with the color calibration slide proposed in [29]. While the use of the color calibration slide ensures that the colors reproduced by the different slide scanners are consistent, the present staining correction scheme addresses the colorimetric differences in histopathology images which are mainly caused by staining variations in histology slides.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The staining correction we presented in this paper can be used in conjunction with the color calibration slide proposed in [29]. While the use of the color calibration slide ensures that the colors reproduced by the different slide scanners are consistent, the present staining correction scheme addresses the colorimetric differences in histopathology images which are mainly caused by staining variations in histology slides.…”
Section: Discussionmentioning
confidence: 99%
“…Previous works have shown that the accuracy of image analysis is sensitive to variations in the colorimetric attributes of the image [17,18,21,29,30]. The box plots in Fig.…”
Section: Tissue Classificationmentioning
confidence: 98%
See 1 more Smart Citation
“…[3] The high quality and consistency of whole slide images are becoming more important with an increase in the computer aided diagnostics. Recent works[456] propose methods to standardize color distribution of the whole slide images in a post-processing step. However, the workflow standardization is non-trivial mainly because it requires formalization of multiple processes, for example, specimen preparation, scanning, image postprocessing and displaying.…”
Section: Introductionmentioning
confidence: 99%
“…All these issues may interfere with image analysis algorithms [22]. Some recent advances have been done for color standardization in WSI by means of using a color calibration slide [23]. A solution to overcome tissue fold artifacts by color enhancement techniques has also been developed by the same authors [24].…”
Section: Image Analysis In Digital Pathologymentioning
confidence: 99%